Significance of Vitamin C in Cancer Prevention and Therapy: A Review - Mardones, Lorena (Disease and Health Research: New Insights Vol. 6, 2024)
The relationship between vitamin C and cancer is still being studied and is associated with antioxidant, pro-oxidant, and gene expression regulator properties. Vitamin C is a water-soluble antioxidant associated with the prevention of the common cold and is also a cofactor of hydrolases that participate in the synthesis of collagen and catecholamines and in the regulation of gene expression. This review explores the role of vitamin C in cancer clinical trials and the aspects to consider in future studies, such as plasmatic vitamin C and metabolite excretion recording, and metabolism and transport of vitamin C into cancer cells. The reviewed studies show that vitamin C intake from natural sources can prevent the development of pulmonary and breast cancer and that vitamin C synergizes with gemcitabine and erlotinib in pancreatic cancer. Vitamin C homeostasis is controlled mainly by four regulatory processes: (i) intestinal absorption (bioavailability), (ii) accumulation and distribution in tissues, (iii) utilization and recycling, and (iv) renal excretion and reabsorption. In vitro assays reveal that vitamin C synergizes with DNA-methyl transferase inhibitors. However, vitamin C was not associated with cancer prevention in a Mendelian randomized study. The effects of vitamin C on cancer progression depend on the route of administration. It is concluded that the role of vitamin C in the prevention and treatment of cancer is still an ongoing area of research. It is necessary that new phase II and III clinical trials be performed to collect stronger evidence of the therapeutic role of vitamin C in cancer. Clinical trials with Intravenous Ascorbic Acid as a co-adjuvant in radiotherapy or chemotherapies with gemcitabine, erlotinib, and DNA Methyltransferases inhibitors are assays in development with promising results. It is expected that new studies will reveal more about the mechanisms of the anti-cancer action of vitamin C, with new, well-structured phase II and III clinical trials performed to confirm its proposed beneficial effect on cancer prevention and treatment.